A case of desmoid tumor co-existing with recurrent squamous cell carcinoma in the larynx. Issue 3 (June 2017) - Shinohara, Shogo; Suehiro, Atsushi; Kikuchi, Masahiro; Harada, Hiroyuki; Kishimoto, Ippei; Imai, Yukihiro
Abstract: Extra-abdominal desmoid tumor, also known as aggressive fibromatosis, has aggressive behavior with local infiltration and tendency for recurrence. Though head and neck is reported to be one of the most common sites, a desmoid tumor in the larynx is extremely rare. A 67-year-old male visited our hospital with prolonged hoarseness and received laryngo-microsurgery with the diagnosis of laryngeal polyp. After the operation, he eventually developed a laryngeal squamous cell carcinoma with papilloma, confirmed by second laryngo-microsurgery and received radiation therapy. After the third laryngo-microsurgery to remove residual papilloma, white irregular mass appeared on the right vocal cord and grew rapidly beneath the glottis, causing dyspnea. After 2 additional laryngo-microsurgeries, he was diagnosed having the dermoid tumor co-existing with recurrent squamous cell carcinoma. He underwent near-total laryngectomy and is currently alive without disease, speaking using a vocal shunt. Only five cases of the desmoid tumors arising in the adult larynx have been reported in the English literature. In this case, repeated surgery and radiation were suspected as the causes. Also, the present report is the first to describe desmoid tumor co-existing with recurrent squamous cell carcinoma in the larynx.